Breast cancer detection based on CPW antenna - Slimi, Marwa (2019)
This work presents the design of CPW antenna for microwave tumor cell detection. The simulation results of the antenna performance in free space using CST-MWS are shown at 4.5 GHz. In order to study, the influence of the antenna movement on its electrical properties during breast cancer diagnosis, the CPW antenna is placed at a distance of 32 mm from the surface of the breast phantom with and without tumor cells by using different positions of the antenna to cover the entire breast surface and with various cross sections of the breast phantom. The tumor is represented by the sphere of diameter equal to 10 mm. In this paper, three interesting antenna parameters are analyzed, the return loss, the radiation pattern and the E-field inside the breast. This study shows good results to can detect the incidence of the tumor at 4 GHz. Comparing these results without and with tumor, it can be said that increasing the angle between the antenna and the breast phantom (from 0° to 60°), the return loss increases from -17 dB to -19.34 dB in 0°, from -15.37 dB to -19.28 dB in 30° and from -12.18 dB to -15.44 dB in 60°. The gain increases from 4.22 dB to 4.26 dB in 0°, from 1.13 dB to 1.2 dB in 30° and from 3.91 dB to 4.06 dB in 60°. In addition, to the increase of the e-field values inside the different cross sections of the breast phantom.